2022
DOI: 10.1038/s42003-022-03591-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term hematopoietic stem cells as a parasite niche during treatment failure in visceral leishmaniasis

Abstract: Given the discontinuation of various first-line drugs for visceral leishmaniasis (VL), large-scale in vivo drug screening, establishment of a relapse model in rodents, immunophenotyping, and transcriptomics were combined to study persistent infections and therapeutic failure. Double bioluminescent/fluorescent Leishmania infantum and L. donovani reporter lines enabled the identification of long-term hematopoietic stem cells (LT-HSC) as a niche in the bone marrow with remarkably high parasite burdens, a feature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 91 publications
2
28
0
Order By: Relevance
“…Blocking studies in future will reveal the mechanism of entry of L. donovani parasites into HSCs. Recent studies showing the uptake of L. donovani / L. infantum parasites in human (Carvalho-Gontijo et al, 2018) and murine HSCs (Dirkx et al, 2022) further validates our results obtained by dual scRNA-Seq analysis. Our in vivo studies from Balb/C mice that has been infected with L. donovani DsRed parasites for 9 months showed that Ter-119-CD11b-CD45R-CD5-CD3-Gr1-Sca-1+c-Kit+ HSCs remain infected with the parasites strengthens the hypothesis that HSCs maybe a source of persistent infection due to their longevity.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Blocking studies in future will reveal the mechanism of entry of L. donovani parasites into HSCs. Recent studies showing the uptake of L. donovani / L. infantum parasites in human (Carvalho-Gontijo et al, 2018) and murine HSCs (Dirkx et al, 2022) further validates our results obtained by dual scRNA-Seq analysis. Our in vivo studies from Balb/C mice that has been infected with L. donovani DsRed parasites for 9 months showed that Ter-119-CD11b-CD45R-CD5-CD3-Gr1-Sca-1+c-Kit+ HSCs remain infected with the parasites strengthens the hypothesis that HSCs maybe a source of persistent infection due to their longevity.…”
Section: Discussionsupporting
confidence: 86%
“…Many public resources, such as ImmGen and the Human Cell Atlas, provide the required data for the desired cell populations, yet there is no information available for parasitized cell types, which would be required to deconvolve infected from uninfected cells. Logically, past attempts of deconvolution have compared results between infected and uninfected tissue (Dirkx et al, 2022). However, deconvolution of cell populations derived an infected host using prior knowledge of cell types from uninfected host remains a challenge of this approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence of persister forms in leishmaniasis. PKDL is an example of relapse occurring after treatment and apparent cure of VL with antimonials in India [ 122 , 123 ].…”
Section: Current Treatments Against Trypanosomatidsmentioning
confidence: 99%
“…Mef2c has been demonstrated to be associated with enrichment of classical activated macrophages that is M1 and promotes pro-inflammatory cytokine production in leishmaniasis (Dirkx et al, 2022), it was observed from patient samples that synthesis of Mef2c is associated with NFAT5 canonical pathway which also in turn regulates NFAT5 mediated immune response, TNFα is the upstream regulator of MEF2C (Salih et al, 2017). Another transcription factor which was enriched through TFTG network was Isl1, although much is not known about the role of this gene in leishmaniasis nonetheless, it consists of LIM domain is essential for regenerating T cell in spleen in leishmaniasis (Golub et al, 2018).…”
Section: Nfat5 Controls Cellular Signaling and Epigenetically Regulat...mentioning
confidence: 99%